1976
DOI: 10.3109/00016357608997711
|View full text |Cite
|
Sign up to set email alerts
|

Turku sugar studies V: Final report on the effect of sucrose, fructose and xylitol diets on the caries incidence in man

Abstract: The purpose was to study differences in the caries increment rate as influenced by various sugars. The trial involved almost complete substitution of sucrose (S) by fructose (F) or xylitol (X) during a period of 2 years. There were no significant initial differences as to caries status between the prospective sugar groups; 35 subjects in the S-group, 38 in the F-group, and 52 in the X-group. During the entire study 10 subjects discontinued or were excluded. The clinical and radiographical observer error was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
12

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 7 publications
3
78
1
12
Order By: Relevance
“…Although many classic studies have already demonstrated the association between sugar consumption and caries (Turku Sugar Study, 24 Hopewood House Study, 25 Hereditary Fructose Intolerance 26 and Experimental Caries in Man 27 ), the Vipeholm Study definitively established that the more frequently sugar is consumed, the greater the caries risk. 9 For some decades, a linear relationship between sugar consumption and caries experience has been observed, 28 and restricting sugar intake has played an important role in caries prevention.…”
Section: Diet and Health Promotionmentioning
confidence: 99%
“…Although many classic studies have already demonstrated the association between sugar consumption and caries (Turku Sugar Study, 24 Hopewood House Study, 25 Hereditary Fructose Intolerance 26 and Experimental Caries in Man 27 ), the Vipeholm Study definitively established that the more frequently sugar is consumed, the greater the caries risk. 9 For some decades, a linear relationship between sugar consumption and caries experience has been observed, 28 and restricting sugar intake has played an important role in caries prevention.…”
Section: Diet and Health Promotionmentioning
confidence: 99%
“…Finlandiya'da 1970'lerde gerçekleştirilen Turku çalışmasında, günlük diyette sakkarozun yerine fruktoz veya ksilitol bulunması durumunda diş çürüklerinin oluşma durumu araştırılmıştır. Çalışma sonuçlarına göre; sakkaroz ve fruktozun diyette bulunduklarında diş çürüğüne sebebiyet vermeleri arasında bir fark gözlenmezken, günlük diyette sakkaroz yerine ksilitol kullanımının önemli oranda diş çürüğünü azalttığı tespit edilmiştir [36,39].…”
Section: Dental Plak Oluşumunda Gıdaların Etkisiunclassified
“…In 2011, over 1,400 students were admitted into the dental colleges of Kerala. 2 The private sector remains the major employment provider for these graduates as the total existing job opportunities in government is 243 of which 144 are in government run dental colleges. 1 The demand for dental treatment in Kerala is high owing to a low dentistto-population ratio and increased awareness among the population.…”
Section: Plenty and Scarcitymentioning
confidence: 99%
“…2 The private practice sector in these cities has become saturated whereas the majority of rural populations do not have access to primary dental care. 3 This co-existence of plenty and scarcity simultaneously makes it likely that dentist protests like that in Kerala may happen in other parts of India in the near future.…”
Section: Plenty and Scarcitymentioning
confidence: 99%